Impactul Probioticelor asupra Sistemului Imunitar: O Perspectivă Holistică - Mihai Folescu; Eugenia Dumitrescu; Sergiu Orășan - Alic; Florin Muselin; Alexandru O. Doma; Daiana Ionela Cocoș; Romeo T. Cristina (Medicamentul Veterinar, 2023)
The human immune system is a complex network of cells, tissues and organs that work together to defend the body against harmful invaders. In recent years, there has been increasing interest in the role of probiotics in regulating immune responses. Probiotics are defined as live microorganisms that benefit the health of the host when administered in adequate amounts thus they have attracted attention for their potential to positively influence the functioning of the immune system. The gastrointestinal tract is home to trillions of microorganisms, known as the gut microbiome, which play a fundamental role in shaping the immune system. Probiotics, mainly bacteria such as Lactobacillus and Bifidobacterium species, are integral components of this microbial community. The interaction between probiotics and the immune system occurs through the gastrointestinal-immune axis, a two-way communication system between the digestive tract and the immune system.